Conservar extrañas maravillas del carbón como estrategia vecinal de emancipación - Fluxá Álvarez-Miranda, Bárbara (Re-visiones, 2024)
In this contribution, I briefly present some processes and results of the collaborative project El aula de las maravillas (The Classroom of Wonders), developed in the mining basins of Fabrero, in El Bierzo (León), currently without industrial activity and undergoing environmental restoration. This project puts into practice the potential of interdisciplinary cultural action centered around the rescue and conservation of an exceptional collection of Carboniferous fossils found in the mine as a driver of emancipation, social and environmental transformation to generate new cultural imaginaries and heritage. It fosters a dialogue between contemporary art and museology; ecological history and mining memory; academic geology or paleontology and the citizen science of some town residents, now amateur paleobotanists.
Keywords: interdisciplinary artistic strategies; mining town; community action; citizen paleobotanical science; cabinet of wonders